2-Hydroxy, 4-n-Butoxy Acetophenone Oxime as a Reagent for Gravimetric and Spectrophotometric Determination of Copper(II) - Talati, J.D.; Patel, P.K. (Asian Journal of Chemistry, 2010)
2-Hydroxy, 4-n-butoxy acetophenone oxime (C12H17O3N) has been used for gravimetric estimation of Pd(II), Cu(II), and Ni(II) from their mixtures at pH values of 1.5, 3.5, 5.5 respectively. The reagent can also be used for extraction spectrophotometric determination of copper(II) in the pH range 6.0–10.0. The mole ratio, slope ratio and Job's method show the metal:ligand ratio in the complex to be 1 : 2 with a stability constant of 2.4 x 109. The yellowish green complex formed and extracted in benzene layer obeys Beer's law up to 326.7 ppm. The optimum concentration range, the photometric sensitivity and molar absorptivity are found to be 197.2–326.7 ppm, 0.58 μg / cm2 and 108 L mole–1cm–1 at 650 nm respectively . The complex is fairly stable for 24 h and 50ºC (ΔG = –12.96 Kcal/mole).